Correlation between Hoff test performance, body composition and aerobic and anaerobic fitness in professional soccer players - Zagatto, Alessandro Moura [UNESP]; Miyagi, Willian Eiji [UNESP]; Brisola, Gabriel Motta Pinehiro [UNESP]; Milioni, Fabio [UNESP]; Silva, Adelino Sanchez Ramos da; Santiago, Paulo Roberto Pereira; Papoti, Marcelo (Springer Nature, 2015)
Purpose The purpose of the study was to investigate a possible association between the distance covered in the Hoff test with parameters of maximal oxygen uptake (V_O2MAX), anaerobic threshold, anaerobic fitness, and body composition of professional adult soccer players. Methods Twenty-five professional soccer players (20 ± 3 years) participated in the study. On different days the athletes performed: a graded incremental exercise test in a laboratory to measure V_O2MAX; a specific soccer field test called the Hoff test; a running anaerobic sprint test (RAST); an incremental test on an oval circuit to determine the velocity relative to anaerobic threshold (VAnT) and an estimation of body composition. Results The average V_O2MAX corresponded to 4.1 ± 0.1 L min-1 (54.1 ± 1.2 mL kg-1 min-1 ). The average distance covered during the Hoff test was 1,442.4 ± 30.0 m. The distance covered during the Hoff test showed significant correlations with absolute and expressed in an appropriated scale V_O2MAX (r = 0.44, p = 0.02; r = 0.42, p = 0.02, respectively) while no significant differences were found with body composition, VAnT and RAST variables. Conclusions The present study demonstrated that the distance covered during the Hoff test has weak correlation with V_O2MAX determined in treadmill running, and no correlation with VAnT, body composition and RAST outcomes, probably due to the non-specificity of the proposed tests when associated with the Hoff test.
Keywords: Aerobic power; Anaerobic power; Soccer evaluation; Specificity; Anthropometry